3D-mixed-mode-loading: material characteristic values and criteria’s validity - H. A. Richard; A. Eberlein (Fracture and Structural Integrity)
In many structures and components cracks, which are exposed to a 3D-mixed-mode-loading, occur due to multiaxial loading situation. A reliable evaluation of those components requires fracture mechanical criteria validated by experimental investigations. Within this article 3D-mixed-mode criteria for static as well as cyclic loadings will be presented. Experiments for pure mode I-loading, pure mode II-loading, pure mode IIIloading and 2D- as well as 3D-mixed-mode-loading combinations are performed using specially developed specimens and loading devices. By comparing the experimental results with criteria a widely validity of criteria and a generally conservative behaviour are revealed.